2003
DOI: 10.1021/jp022131n
|View full text |Cite
|
Sign up to set email alerts
|

Structures, Intramolecular Rotation Barriers, and Thermochemical Properties of Methyl Ethyl, Methyl Isopropyl, and Methyl tert-Butyl Ethers and the Corresponding Radicals

Abstract: Structures and thermochemical properties, ∆H°f 298 , S°(T), and C p (T) (50 e T/K e 5000) of three ethers and the corresponding radicals were determined by ab initio and density functional calculations. Molecular structures and vibration frequencies were determined at the B3LYP/6-31G(d,p) and MP2/6-31G(d,p) levels, with single point calculations for the energy at the B3LYP/6-311+G(3df,2p) and MP2/6-311+G(2df,2p) levels, respectively, and with composite methods CBSQ and G3(MP2) with B3LYP/6-31G(d,p) and MP2/6-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 41 publications
6
45
0
Order By: Relevance
“…This result corresponds to the conclusions of Wang and Frenklach, Aihara et al, Cioslowski et al and Barckholtz et al [24][25][26][27] The modified neglect of differential overlap (MNDO) study of Chen et al predicted that the CÀH bond of the lone hydrogen in anthracene was weaker than that of a CÀH bond in benzene, but this might be attributed to the low level of theory that was adopted. [46] Our results correlate with the fact that the out-of-plane bending mode of lone hydrogens at 11.2 mm is very strong in the infrared emission spectra of many ultraviolet-excited nebulae. [68,69] It is also noteworthy that Lardin, Squires and Wenthold recently performed an experimental study to determine the BDEs of CÀH bonds in naphthalene.…”
Section: Bdes Of Aryl Radicals For Pahssupporting
confidence: 82%
See 1 more Smart Citation
“…This result corresponds to the conclusions of Wang and Frenklach, Aihara et al, Cioslowski et al and Barckholtz et al [24][25][26][27] The modified neglect of differential overlap (MNDO) study of Chen et al predicted that the CÀH bond of the lone hydrogen in anthracene was weaker than that of a CÀH bond in benzene, but this might be attributed to the low level of theory that was adopted. [46] Our results correlate with the fact that the out-of-plane bending mode of lone hydrogens at 11.2 mm is very strong in the infrared emission spectra of many ultraviolet-excited nebulae. [68,69] It is also noteworthy that Lardin, Squires and Wenthold recently performed an experimental study to determine the BDEs of CÀH bonds in naphthalene.…”
Section: Bdes Of Aryl Radicals For Pahssupporting
confidence: 82%
“…[24] Only three classes were suggested due to the limited dataset considered. Other interesting references concerning BDEs of aryl radicals are the works by Chen et al, Aihara et al and Cioslowski et al [46,25,26] The latter reference is the closest to our work since the results are also based on ab initio techniques.…”
Section: Bdes Of Aryl Radicals For Pahsmentioning
confidence: 61%
“…Speybroeck et al reported overall good agreement between experimental and calculated entropy and heat capacity values for n-alkanes, treating internal rotors without coupling [22]. Chen and Bozzelli [23] have also shown very good agreement between calculated and experimental o ( ) and ( ) for ethers and ether radicals when internal rotation contributions were included. The potential energy as function of the dihedral angle is calculated by varying the torsion angle in 30…”
Section: Thermodynamic Propertiesmentioning
confidence: 88%
“…The values from X//MP2(full)/6-31G(d,p) (X=G3(MP2), CBS-Q, CBS-4 and CBS-lq) are listed in [35]; (C=CCOH) = −29.55±0.35 [36]; (C=CCOOH) = −13.59±0.14 [37]; (C2COH) = −65.07±0.22 [38]; (C2COOH) = −48.99 ± 0.32 [39]; (CCOOH) = −39.70 ± 0.30 [23]; (CCOO•) = −6.72 ± 2.3 [40]; (1,4-cyclohexadiene) = 25.04 ± 0.14 [41]; (1,3-cyclohexadiene) = 25.00 ± 0.15 [41]; (cyclohexene) = −1.03±0.23 [42]; (benzene) = 19.82±0.12 [43]; (phenol) = −23.03±0.14 [44]; (toluene) = 11.95±0.15 Entropies and heat capacities from 50 K to 5000 K were calculated using the rigid-rotor-harmonic-oscillator approximation based on scaled vibrational frequencies (the two torsion frequencies corresponded to -OO and -OH rotors are excluded), molecular mass, and moments of inertia of the optimized B3LYP/6-31G(d, p) structures. The ROTATOR program is used to calculate internal rotor energy levels from the structure and the calculated one-dimensional uncoupled intramolecular rotation potential energy curves [18,19].…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%
“…Even though the formation of ether bonds entails a higher crosslinking degree, this type of bond can easily rotate. [23] Additionally, due to the random distribution of chemical functions, the structure of plasma materials is of amorphous nature. These two conditions allow for the local reorganization of chain segments during the formation of dipole-dipole bonds between the penetrating water molecules, and the oxygen atoms in the C-O-C functions.…”
Section: Swelling Of the Bulk Layermentioning
confidence: 99%